Potential for Recycling Nutrients from Biosolids Amended with Clay and Lime in Coarse-Textured Water Repellence, Acidic Soils of Western Australia - Sanjutha Shanmugam; Lynette K. Abbott (Applied and Environmental Soil Science)
Application of biosolids in soils is an efficient method of recycling nutrients from biosolids and it is considered even safer when it is modified after mixing and diluting with other suitable soil organic amendments. A variety of soil organic amendments, such as green manures and composts, are used for modifying and co-composting with biosolids. However, these may not be considered as appropriate biosolids disposal and remedial measures for soils with unique problems such as low soil pH, water repellence nature, and poor water and nutrient retention capacities due to soil textural issues. Historically, soil amendments such as lime, clay, and recently biochar are being applied for such problematic soils at Western Australia and these researches focused mostly on improvement in soil physical and chemical properties. However, studies with potential for applying modified biosolids with these amendments are not complete yet. This review focused on identifying such gaps in these studies from over 170 peer-reviewed key research and review articles published over decades to latest in these areas.